Prevalence Of Psychiatric Morbidity Among 6 To 14 Years Old Children - Anita; Gaur D. R; Vohra A. K; Subash S; Khurana Hitesh (Wolters Kluwer Medknow Publications, 2003)
Research questions: What is the prevalence of psychiatric morbidity among 6 to 14 years old children? Objectives: 1. To study the prevalence of psychiatric disorders in children of 6-14 years of age in rural and urban areas. 2. To study the pattern of psychiatric disorders and associated socio-demographic variables. Study design: Cross-sectional. Setting and Participants: 400 children each from urban and rural field practice areas under the department of Social and Preventive Medicine, PGIMS, Rohtak. Statistical analysis: Percentages, Chi-square test. Results: Prevalence of Psychiatric disorders in children was found to be 16.5%. Conduct disorder was the most common psychiatric disorder observed (4.5%) in these children followed by mental retardation (3.25%). Prevalence was more in male children (18.37%) than in female children (14.44%), more common among scheduled caste children (18.4%), also in children who belonged to nuclear families (17.35%).